2015
DOI: 10.15713/ins.jcri.34
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of orofacial pain: A retrospective study

Abstract: Background: The orofacial pain is a pervasive situation either of somatic or psychological etiology arising from the structures supplied by the trigeminal nerve. Identifying the cause of orofacial pain goes a long way in diagnosis and treatment. Objectives: To evaluate the cause of pain among the subjects reporting to the dental college. Materials and Methods: A retrospective study was conducted on a group of patients with persistent facial pain with an ebb to respond properly to previous treatments were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
6
0
1
Order By: Relevance
“…In case of persistent or recurrent pain, TMD may follow a chronic course . It is reported that the prevalence of TMD pain in the general population ranges from 4·0% to 15·0% in countries around the world .…”
Section: Introductionmentioning
confidence: 99%
“…In case of persistent or recurrent pain, TMD may follow a chronic course . It is reported that the prevalence of TMD pain in the general population ranges from 4·0% to 15·0% in countries around the world .…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Shetty et al 15 higher prevalence of orofacial pain was witnessed among the female patient group. Most prevalent reason for orofacial pain in the subjects observed was pulpitis with 946 or 43% of the patients.…”
mentioning
confidence: 87%
“…Classification and epidemiological studies of orofacial pain have a prevalence of up to 26% (Shetty et al 2015). The prevalence of orofacial pain in several countries is reported by where orofacial pain is known to be more than a quarter of the adult population (Smiljić et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of orofacial pain in 3 countries, namely Hong Kong, Indonesia, or Brazil, known to reach more than 40% (Maulina et al 2014). Other studies report (Shetty et al 2015,) that orofacial pain affects 10% of the adult population and is more likely to occur in women than in men. This study states that orofacial pain is caused by various factors, but the most commonly reported causes of orofacial pain are pulpitis (43%), pain due to periodontal abnormalities (32%), pericoronitis (13%), and temporomandibular joint disorders as many as 8% (Shetty et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation